Community adult education for a social vaccine in pandemic and post pandemic times (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
This article argues for a 'social vaccine' in pandemic times that underpins the fourbasic requirements for global health and equity to flourish by providing a life withsecurity, opportunities that are fair, a planet that is habitable and supportsbiodiversity and governance to ensure resources are fairly distributed (Baum andFriel, 2020). By a ‘social vaccine’ I do not mean a biological vaccine that isproduced in laboratories and injected in arms to produce immunity to the COVID19virus. A ‘social vaccine’ is an antidote to counteract the consequences and long-termeffects of epidemic upheaval, designed from below in participatory and dialogicalrelationships with those worst affected by its consequences. This article argues thatcommunity adult education, which has incessantly prioritised employability skillstraining, should play a pivotal role in providing a ‘social vaccine’ in pandemic andpost-pandemic times. The significance of community adult education is that it seeksto build the curriculum from the inequalities and injustices that people experience intheir everyday lives by providing opportunities for individual and collective change.